2013
DOI: 10.1111/j.1937-5956.2012.01342.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing Risk of Supply Disruptions: Incentives for Capacity Restoration

Abstract: A supplier facing the prospect of disruption has to decide whether or not to invest in restoration capability. With restoration capability, if disruption occurs, additional costly effort can be exerted to rebuild capacity, although its outcome is uncertain. We study how a firm (buyer) can use incentive mechanisms to motivate a supplier's investment in capacity restoration, and compare this approach with the traditional approach of diversifying part of the order to an expensive but reliable supplier. Under a Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
85
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(86 citation statements)
references
References 38 publications
0
85
0
1
Order By: Relevance
“…• Ordered quantity and frequency (OQF): Majority of the suppliers look for the quantity ordered and frequency of the orders placed by the manufacturer as the basis to favourably reciprocate (Xia et al, 2008;Wee and Widyadana, 2013;Hu et al, 2013).…”
Section: • Prompt Payments Of Outstanding Bills (Ppo)mentioning
confidence: 99%
“…• Ordered quantity and frequency (OQF): Majority of the suppliers look for the quantity ordered and frequency of the orders placed by the manufacturer as the basis to favourably reciprocate (Xia et al, 2008;Wee and Widyadana, 2013;Hu et al, 2013).…”
Section: • Prompt Payments Of Outstanding Bills (Ppo)mentioning
confidence: 99%
“…For instance, one branch of research focused on multiple sourcing which was particularly effective against supply disruption when some suppliers can guarantee delivery [5,6]. Liker and Choi [7] found that Honda and Toyota adopted dual source and worked with one or both suppliers to improve performance.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of agility is to quickly respond to short-term changes in demand and supply and to smoothly handle external disruptions (Charles, 2010). Supply disruption is infrequent risk but has large impact on the whole supply chain (Hu et al, 2013), because it could cut off the cash flow and stop the operation of the entire supply chain.…”
Section: Introductionmentioning
confidence: 99%